Solvent solutions: Comparing extraction methods for edible oils and proteins in a changing regulatory landscape. Part 4: Impacts on energy consumption☆ - Carré Patrick; Piofczyk Thomas; Bothe Sarah; dev Borah Chandra; Hadjiali Sara (Oilseeds and fats, crops and lipids)
This study compares various solvents for edible oil extraction, focusing on their energy consumption impacts. The research examines traditional hexane and alternative solvents, using both theoretical calculations and experimental data. The article presents a thermodynamic analysis of solvent-water separation using ChemSep software for rectification simulations. Results show significant differences in energy requirements, with acetone being potentially the most efficient and alcohols (ethanol and isopropanol) requiring substantially more energy at desolventization step. Solvent hold-up in the marc is a crucial factor affecting desolventization energy consumption. Experimental data from a pilot plant study on rapeseed cake extraction is presented, showing higher retention rates for ethanol and isopropanol compared to hexane. For other solvents, retention rates are estimated using the Hansen solubility parameter δh. Energy requirements for meal desolventization are calculated, considering factors such as solvent properties, marc composition, and steam usage. Alternative solvents generally show higher energy consumption compared to hexane. With a hypothetical non-distillation scheme the heat required is +76% for ethanol, +32% for isopropanol, −21% for acetone. It is +42% for the acetone solvent in traditional miscella evaporation. Methyl ethyl ketone (MEK) would require +66%, ethyl acetate 33% and 2-methyloxolane +35% more heat. Dichloromethane and isohexane require a little less energy because of their low boiling point while cyclohexane requires 5% more. The study also discusses the implications of solvent choice on desolventizer-toaster-dryer-cooler (DTDC) design and operation, highlighting potential challenges with high-moisture in the meal resulting from intensive use of direct steam.